The Dutch block of the ESCB multi-country model - Elena Angelini; Frédéric Boissay; Matteo Ciccarelli (European Central Bank (ECB), 2006)
The paper presents the Dutch country block of the ESCB Multi-Country Model (MCM) for the euro area. We show how a theoretical model is translated into an econometric specification and how this specification is in turn estimated and used in the projection exercises of the E(S)CB. The dynamic properties of the model are analyzed and the effects of six exogenous shocks to the economy discussed. The long run simulations performed deliver responses of the baseline economy in line with both macroeconomic theory and practice, from a quantitative and a qualitative point of view.
Keywords: C3; C5; E1; E2; 330; forecast; Multi-country model; Netherlands; Simulation; Makroökonometrie; Wirtschaftsprognose; Simulation; Zentralbank; EU-Staaten; Niederlande